Formative Test Analysis Of Islamic Religious Education Learning Evaluation Practices (Study At SMP Negeri 1 Muara Kemumu) - Yova Atika; Yessy Rahmaniar; Muslim; Deri Wanto; Mirzon Daheri (Indonesian Journal of Pedagogy and Teacher Education, 2023)
The purpose of formative assessments is to monitor and enhance the learning process while assessing the attainment of learning goals. The purpose of this research is to examine formative assessments on assessment procedures in Islamic Religious Education classes at SMP Negeri 1 Muara Kemumu. This study employs a particular kind of field research. This study use a qualitative descriptive method to explain or characterize a phenomenon. The Islamic Education instructor at SMP Negeri 01 Muara Kemumu is the focus of the study. Subsequently, lesson plans and question sheets are acquired from instructor data. Through documentation, interviews, and observation, data were gathered. to determine if formative assessments are appropriate for PAI learning. Techniques for data analysis include data reduction, data visualization, and conclusions or confirmation. Teachers of Islamic Religious Education at SMP Negeri 01 Muara Kemumu served as the study's informants. The study's findings show that Islamic Religious Education instructors at SMP Negeri 01 Muara Kemumu provide formative assessments following the completion of a topic or chapter. However, the only formative assessment that is utilized is a post-test consisting of essays and multiple choice questions.